Triterpenoid Saponins from Rubus ellipticus var. obcordatus - Li, Wei; Fu, Hongwei; Bai, Hong; Sasaki, Tatsunori; Kato, Hiroyoshi; Koike, Kazuo (Journal of natural products (Washington, D.C.), 2009)
Ten new triterpenoid saponins (1−10), named rubusides A−J, and 21 known saponins (11−31) were isolated from the roots of Rubus ellipticus var. obcordatus. The structures of 1−10 were established on the basis of spectroscopic analyses, mainly NMR and MS, and chemical degradations. The compounds demonstrated inhibitory activities against α-glucosidase with IC50 values in the range 0.65−3.09 mM.